Useful maneuvers for precise laparoscopic liver resection. Issue 2 (3rd May 2018) - Chanwat, Rawisak
Abstract: Laparoscopic liver resection has evolved over the past decade and nearly replaced open exploration. This procedure not only provides comparable oncological outcomes, but it also has improved recovery after surgery. Many of the challenges presented by limitations of instruments and techniques have been overcome through adaptations and new developments, and it is possible that the remaining obstacles will be overcome within a few years. Moreover, as surgeons continue to gain experience, their technical knowledge has supported further improvement in minimally invasive approaches. This review examines every important procedures in performing a precise laparoscopic liver resection.